Development Trends of Youth Situation in the National Labour Market and the Methodological Calculation Problems of Labour Market Indicators - Okunevičiūtė Neverauskienė, Laima; Pocius, Arūnas (Ekonomika, 2008)
The objective of the article is to evaluate the situation of youth in the labour market and to reveal the trends of its development, referring to the data of Statistics Department and Lithuanian Labour Market. The methodological calculation problems of youth unemployment indicators are reviewed; the possibilities of employing particular labour market indicators when analysing youth unemployment are discussed; the influence of particular factors on youth unemployment is evaluated. The first part of the article evaluates the position of youth in the labour market of the country and the trends of its development. The analysis allows the conclusion that the employment rate was declining rapidly during the period 1997-2001 (from 36.3% to 22.5%), and then there was stabilisation with insignificant variations of the employment rate indicator. It must be emphasised that youth employment, which temporarily increased in 2002, declined again in 2003-2004 (to 20.3%), reaching its minimum level. Short-term positive changes of youth employment (the indicator increased to 23.7%) showed up in 2005-2006, although this increase was comparatively insignificant and did not compensate the previous significant negative trend. The other trends during a longer period were a decrease of youth activity (employment) and an increase of inactive population in the labour market. The article shows the components (factors) of youth inactivity increase, of which employment decrease had the biggest influence. One more trend observed in the last years is that the youth unemployment rate almost equalled with the analogous the indicator in other age groups. This means that the differences in unemployment rates depending on age significantly decreased. The second part of the article reveals the methodological problems of evaluating the situation of youth in the labour market, highlighting the methodical problems of calculating youth unemployment rate. Also there are analysed other indicators which allow evaluating the situation of youth in the labour market more objectively. The youth unemployment rate, expressed by the percentage of young unemployed people in the labour force of this age bracket does not reflect the real situation in the labour market when speaking about youth as a whole (an age bracket). In 2006, youth labour force covered only about 26% of the state’s youth. Hence, the official indicator of unemployment rate reflects the position of only 26% of youth, and the rest 74% remain outside the assessment. In the authors’ opinion, this is the reason why this usual unemployment rate indicator cannot be the basic indicator generalising the position of youth in the labour market. The third chapter presents an interelation between the indicators of youth situation in the labour market and the other indicators of a particular social economic development of the country. Correlation analysis is one of the alternative ways to describe the interconnection among the indicators that characterise the position youth in the labour market. There were considered many correlation indicators which show that the formal connection among the discussed indicators is not statistically significant. However, calculation of correlation coefficients should be seen as an attempt to estimate the trend of connection between the analysed phenomena. This allows evaluating the existing changes quantitatively and discovering the reasons for the confronting trends. The conclusion is that the relation between the indicator of the unemployed part of young and other indicators is the toughest one, although the increase of the part of youth is not the criterion of unemployment intensity (its rate). On the other hand, the imperfection of the youth unemployment rate is not characteristic of this indicator, and its values of correlation are noticeably higher and in most cases statistically significant in comparison with the other indicators used in the analysis. The dynamics of this indicator, which expresses the increased conditional youth competition possibilities in the labour market, react to essential changes of the social, economic and demographical environment in the best way in most cases. Considering the imperfection of the traditional unemployment rate, which is obvious from the analysis, the authors suggest to employ widely the other indicators characterising youth position in the labour market, which allow evaluating the extent of the phenomenon under analysis more objectively. Moreover, there are suggested the possibilities of calculating a new indicator which characterises youth unemployment - the harmonised youth unemployment indicator - and its application for the assessment of youth position in the labour market. In addition, there is shown that a combination of different indicators (including absolute ones) in the research process should become a more and more important element while evaluating trends of youth unemployment dynamics.